Congenital cardiac defects with 22q11 deletion - Giray, Ozlem; Ulgenalp, Ayfer; Bora, Elçin; Sağin Saylam, Gül; Unal, Nurettin; Meşe, Timur; Hüdaoğlu, Suphi; Erçal, Derya (The Turkish Journal of Pediatrics, 2003)
New cytogenetic techniques have promoted progress in determining the role of chromosomal abnormalities in the cause of congenital cardiac defects. Some patients with congenital cardiac defect have a microdeletion within chromosomal region 22q11, and a majority of them are conotruncal cardiac defects. To determine frequency in our population, we evaluated 36 patients with congenital cardiac defects, 23 of them with conotruncal cardiac defects. Microdeletion of 22q11 was detected in seven of 36 patients (19.4%), and in all deleted cases cardiac pathology was conotruncal.